Proteomics and molecular network analyses reveal that the interaction between the TAT–DCF1 peptide and TAF6 induces an antitumor effect in glioma cells. (3rd January 2020) - Wang, Jiao; Wang, Fushuai; Li, Qian; Wang, Qian; Li, Jie; Wang, Yajiang; Sun, Jiamin; Lu, Dongfang; Zhou, Hong; Li, Shiman; Ma, Sujuan; Xie, Jiang; et al.
Abstract : The TAT–DCF1 protein possesses great potential for the development of glioblastoma therapy through the interaction with TAF6-related pathways. Abstract : Glioblastoma is the most lethal brain cancer in adults. Despite advances in surgical techniques, radiotherapy, and chemotherapy, their therapeutic effect is far from significant, since the detailed underlying pathological mechanism of this cancer is unclear. The establishment of molecular interaction networks has laid the foundation for the exploration of these mechanisms with a view to improving therapy for glioblastoma. In the present study, to further explore the cellular role of DCF1 (dendritic cell-derived factor 1), the proteins bound to TAT–DCF1 (transactivator of transcription–dendritic cell-derived factor 1) were identified, and biosystem analysis was employed. Functional enrichment analyses indicate that TAT–DCF1 induced important biological changes in U251 cells. Furthermore, the established molecular interaction networks indicated that TAT–DCF1 directly interacted with TAF6 in glioma cells and with UBC in HEK293T (human embryonic kidney 293T) cells. In addition, further biological experiments demonstrate that TAT–DCF1 induced the activation of the RPS27A/TOP2A/HMGB2/BCL-2 signaling pathway via interaction with TAF6 in U251 cells. Taken together, these findings suggest that the TAT–DCF1 peptide possesses great potential for the development of glioblastoma therapy through the interaction with TAF6-related pathways and provides further theoretic evidence for the mechanisms underlying the antitumor effects of TAT–DCF1.